Christian Faith: Dogmatics in Outline - Gerrish, B. A. (Westminster John Knox Press, 2015)
Front Cover -- Christian Faith -- Title Page -- Copyright Page -- Table of Contents -- Preface -- Abbreviations -- Appendix -- Selected Bibliography -- Index of Scripture Citations -- Index of Subjects and Persons -- Back Cover.